Wafiyat al a'yan wa anba'u abna'i al zaman - Abi al 'Abbas Shamsuddin Ahmad Ibn Muhammad Ibn Abi Bakr Ibn-Khalikan (Dar al Sadir)
ws.jl.4-8.c.1,jl,3,7.c.1-2,jl.1,3.c.1-3/stoc1, jil1.c.1-2 ; jil.2,3-8=c.1-3 ; jil.3,c.1-4